Biomass-derived carbon porous frameworks: from formation mechanisms to sustainable functional materials - Aleesha Nabhai; Zhengbai Li; Ilma Sang Mainardi; Laura Hernandez Rodriguez; Chandler Ray Sheets; Jinghao Li (Bioresource Technology, 2027)

Uncovering the role of ETS2 in prostate cancer pathogenesis: relationship with p53 and ERG - Laura Segalés; Nuria Juanpere; Marta Lorenzo; Beatriz Casado; Sílvia de Muga; Marta Salido; Alejo Rodriguez-Vida; Lluís Fumadó; Lluís Cechinni; Joaquim Bellmunt; Silvia Hernández-Llodrà (Molecular Biology Reports, 2026)

Inferring the relationship between late Pleistocene-Holocene paleosalinity values and water-level changes from a diatom transfer function: a case study from the Bolivian Altiplano and Laguna Mar Chiquita - Carolina Cuña-Rodriguez; Florence Sylvestre; Mírian Cristina Oliveira da Costa; Laura Perez; Carolina Bueno; Carolina Rodriguez-Pérez; Laura del Puerto; Emmanoel Vieira Silva-Filho; Leticia Gonzalez; Felipe García-Rodríguez; Eduardo L. Piovano (Quaternary Science Reviews, 2026)

Environmental and Economic Life Cycle Assessment of low-tech digesters coupled with gasification technology implemented in a small-scale dairy farm - Kurt Ziegler-Rodriguez; Irene Josa; Liliana Castro; Jaime Jaimes-Estévez; Isabel Daniela Ardila-Beltrán; Laura Camila Romero-Melo; Humberto Escalante; Marianna Garfí (Journal of Cleaner Production, 2026)

Divergent effects of a Bacillus biofertilizer immobilized in guinea pig manure biochar: Boosting productivity vs. enhancing nutritional quality in maca monocultures - Richard Solórzano; Ana Carranza-Ramirez; Nora Vera-Obando; Rosario Javier-Astete; Alberto Arias-Arredondo; Melina Lopez-Rodriguez; Michell K. Arroyo-Julca; Excela Saavedra-Flores; Cinthia Quispe-Apaza; Lizbeth Mamani-Rojas; Juancarlos Cruz; Angel Montes Osorio; et al. (Applied Soil Ecology, 2026)

Modeling the circulation in the Magdalena–Almejas Bay System forced by tides - Susana A. Rodriguez-Melgarejo; Alejandro F. Parés-Sierra; Ana Laura Flores-Morales (Continental Shelf Research, 2026)

Co-construction of social dimensions of environmental quality for urban riverbanks - Natalia Rodriguez; Ángela Juárez; Laura de Cabo (Urban Ecosystems, 2026)

Impact of a recent invader on a freshwater top predator exposure to microplastics and flame retardants - Tiago Coutinho; Bárbara Lages; Ronaldo Sousa; Sara C. Cunha; Laura Rodriguez-Lorenzo; Raul Machado; José O. Fernandes; Begoña Espiña; Amilcar Teixeira; Janeide Padilha (Hydrobiologia, 2026)

Clinical predictors, microbiological profile, and outcomes of bacteremia in patients with cellulitis: a 6-year retrospective cohort study - Ana Cotos Suárez; Amparo López-Bernus; Montserrat Alonso-Sardón; Virginia Velasco Tirado; Laura Sancha Domínguez; Beatriz Rodriguez Alonso; Josue Pendones Ulerio; Juan Luis Muñoz Bellido; Moncef Belhassen-García (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Background Cellulitis is a common cause of hospital admission, yet the clinical relevance and predictors of bacteremia remain incompletely characterized. Identifying patients at risk of bloodstream infection may help optimize diagnostic strategies and clinical management. Methods We conducted a retrospective observational study at a tertiary-care hospital including all consecutive patients hospitalized with cellulitis between January 2019 and December 2024. Patients without blood cultures were excluded. Clinical severity was stratified using the CREST classification. Microbiological data, antibiotic therapy, hospital outcomes, and follow-up at 1 and 3 months were analyzed. Results Among 311 episodes included, bacteremia was confirmed in 46 cases (14.8%). Patients with bacteremia showed significantly higher clinical severity at admission, with CREST grades III–IV present in 56.5% compared with 36.6% in non-bacteremia patients ( p < 0.001). Sepsis occurred in 65.2% of bacteremia cases versus 24.5% of non-bacteremia cases ( p < 0.001). Bacteremia was associated with longer hospital stay (18 ± 18.3 vs 13 ± 9.7 days; p = 0.003) and more frequent antibiotic modifications during admission ( p = 0.023). Streptococcal species and Staphylococcus aureus showed a higher propensity for bloodstream invasion. In-hospital mortality was higher among bacteremia patients (13.0% vs 7.9%), although the difference was not statistically significant. Three-month mortality reached 14.3% in the bacteremia group compared with 9.9% in non-bacteremia patients. Conclusion Bacteremia complicating cellulitis is uncommon but associated with greater clinical severity, longer hospitalization, and increased therapeutic complexity. Severity stratification tools such as CREST may assist in identifying patients at increased risk of bacteremia; however, given their limited discriminatory performance, they should not be used in isolation to guide blood culture collection or other clinical decisions.

Genomic and functional analysis of compost-isolated Bacillus strains with antagonistic activity against Fusarium oxysporum f. sp. lycopersici - Julieta Rodriguez-Ambrogio; Marilina Fernandez; Walter Ferrari; Mariana Vezza; Ana Laura Villasuso (European Journal of Plant Pathology, 2026)

Machine learning-assisted single-cell Raman imaging for rapid, sensitive detection and intracellular mapping of carotenoids in plant cell cultures - Bárbara A. Rebelo; Ensieh Iranmehr; Begoña Espiña; Laura Rodriguez-Lorenzo; Rita Abranches (Plant Cell Reports, 2026)
Key message CRaman imaging combined with a multi-layer perceptron neural network enables non-destructive, label-freeclassifi cation of tobacco BY-2 cells based on carotenoid composition. Abstract Carotenoids are natural tetraterpenoid pigments with important nutritional properties and broad industrial applications. Enhancing their production in plant-based biofactories offers a sustainable alternative to current manufacturing processes. In this work, we developed a label-free, single-cell analytical platform combining Raman imaging with a multi-layer perceptron neural network to classify tobacco BY-2 cells based on their carotenoid content. Carotenoid standards analysis, including astaxanthin, canthaxanthin, and β-carotene, was performed by surface-enhanced Raman scattering using hydrophobic gold nanostars due to the low concentration available. This analysis allowed the assignment of characteristic Raman peaks, specifically at 1160 cm −1 and 1520 cm −1 , of key carotenoids and their identification inside of the cells by Raman imaging. The Raman fingerprints were correlated with carotenoid profiles obtained by HPLC, enabling accurate differentiation between wild-type and transgenic cell lines. In the analyzed transgenic lines, carotenoids accumulated in vesicle-like structures near the nucleus and along the cytoplasmic membrane. This method provides a non-destructive, label-free approach with high classification accuracy and sorting potential based on carotenoid composition, and may be a useful tool for plant synthetic biology and metabolic engineering.

Stomach content analysis reveals how urbanization shapes the trophic and taxonomic structure of macroinvertebrate communities in an Andean river - Gisela Alancay; Nelly Vargas Rodriguez; Laura Pereyra (Hydrobiologia, 2026)

Associations of Blood Lead Concentrations with Ferritin, Vitamin B12, and Homocysteine Levels in Mexican Preschool Children: A Nationally Representative Study - Liliana Garcia-Rodriguez; Laura Danae Díaz-Cuenca; Ma. Elena Moreno-Godínez; Eugenia Flores-Alfaro; Cristian Oswaldo Bravo-Nava; Marco Antonio Ramírez-Vargas (Biological Trace Element Research, 2026)

Ambient temperature and homicide mortality in 307 Latin American cities: A case time series design - Sara Lopes de Moraes; Daniel A. Rodriguez; Leah H. Schinasi; Josiah L. Kephart; Iryna Dronova; Maryia Bakhtsiyarava; Waleska Teixeira Caiaffa; Karla Rangel-Moreno; Laura A. Rodriguez-Villamizar; Marie O'Neill; Amélia Augusta de Lima Friche; Astrid Berena Herrera López; et al. (Environmental Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Activation of Toll-like receptor 2 reveals microbial contamination beyond endotoxins on micro- and nanoplastics - Øyvind P. Haugen; Itziar Polanco-Garriz; Victor Alcolea-Rodriguez; Raquel Portela; Rita Bæra; Hamed Sadeghiankaffash; Jana Hildebrandt; Dmitri Ciornii; Korinna Altmann; Francesco Barbero; Ivana Fenoglio; Julián J. Reinosa; et al. (Toxicology in Vitro, 2026)

Exposure to low-dose ionizing radiation and dementia mortality in Canadian nuclear power plant workers - Brianna Frangione; Laura A. Rodriguez Villamizar; Ian Colman; Franco Momoli; Estelle Davesne; Lydia Zablotska; Cheryl E. Peters; Paul Demers; Minh Do; Tim Prendergast; Philippe Prince; Paul J. Villeneuve (Environmental Research, 2026)

Comparative genome-wide association study shows single-nucleotide polymorphic loci associated with resistance to Meloidogyne incognita, Fusarium oxysporum f. sp. phaseoli, and their co-infection in common bean - Maria Laura Urbano Nascimento; César Júnior Bueno; Carlos Eduardo Rossi; Antônio Augusto Franco Garcia; Maria Lúcia Carneiro Vieira; Luís Eduardo Aranha Camargo; Alisson Fernando Chiorato; Sérgio Augusto Morais Carbonell; Monica Rodriguez; Luciana Lasry Benchimol-Reis (Planta, 2026)
Main conclusion The genetic architecture underlying co-infection with Meloidogyne incognita and Fusarium oxysporum f. sp. phaseoli differs from that observed when these pathogens are evaluated individually. Abstract Common bean ( Phaseolus vulgaris L.) yield is threatened by simultaneous infection with the root-knot nematode Meloidogyne incognita (Mi) and Fusarium oxysporum f. sp. phaseoli (Fop). Root-knot nematodes are believed to intensify the severity of Fusarium wilt in common bean, and specific genomic regions are understood to be associated with the host response, whether conferring susceptibility or resistance. To elucidate the genetic mechanisms of this interaction, phenotypic traits were evaluated in greenhouse trials, followed by associative mapping using a genome-wide association study (GWAS) approach. The plant material consisted of a core collection of 180 common bean genotypes from the Agronomic Institute (IAC, Campinas, Brazil) diversity panel. The effects of Fop and Mi were evaluated individually and in co-infection. Associative mapping was performed using the Bayesian information and linkage disequilibrium iteratively nested keyway (BLINK) model. When plants were infected with Mi, significant SNPs were detected on chromosomes Pv07, Pv08, and Pv10 based on gall counts. SNPs were detected on Pv05, Pv06, P10, and Pv11 in association with co-infection. Regions associated with egg mass count were detected on Pv02, Pv04, and Pv05. However, co-infection revealed SNPs on chromosomes P10 and Pv11. Three SNPs were associated with Fusarium wilt–two on Pv07 and one on Pv08. The genomic regions and markers associated with resistance to Mi and Fop provide new resources for advancing understanding of host–pathogen relationships in these important pathosystems.

Unveiling the temperature-dependent reaction dynamics of Li3BO3: Formation and carbonation mechanisms via in situ synchrotron XRD - María José Orozco; María Laura Grasso; Pedro Alonso-Sánchez; Federico Cova; María Laura Rodriguez; María Valeria Blanco; Fabiana C. Gennari (Chemical Engineering Journal, 2026)

Systematic review update of organisational-level mental health promotion interventions: evidence from healthcare, construction, and telework-based mobile work settings - Eleftherios Giovanis; Oznur Ozdamar; Birgit Aust; Johanna Cresswell-Smith; Arlinda Cerga Pashoja; Caleb Leduc; Andrea Sinesi; Carolina Piña; Chantal Van Audenhove; Gentiana Qirjako; Victoria Ross; Margaret Kenneally; et al. (International Archives of Occupational and Environmental Health, 2026)

Indirect exposure to organophosphate pesticides and its possible growth disorders in children of farmers in Northwest Mexico - Estefanía Ochoa-Ruiz; Aarón Israel Moreno-García; Daniel Alejandro Licea-Espinoza; Gisela Pineda-García; Krysta Paola Carranza-Ambriz; Kenya Karina Soto-Rodriguez; Arnold García-Ledezma; José Manuel Cornejo-Bravo; Ana Laura Martínez; Eleonora Mondani; Aracely Serrano-Medina (International Archives of Occupational and Environmental Health, 2026)
Purpose This study investigated the correlation between growth disorders and indirect pesticide exposure in children of farmers. Methods A cross-sectional study was conducted with 134 children of farmers occupationally exposed to organophosphate pesticides in the ejido Venustiano Carranza, an agricultural community in San Quintín, Baja California, Mexico. These children were compared with a control group of 56 unexposed children. Anthropometric measurements and biochemical analyses were performed in both groups to evaluate renal, hepatic, and nutritional profiles. Hormonal profiles were quantified using ELISA techniques. Cholinesterases are quantified using known colorimetric methods. Food security was also analyzed through a dietary diversity study, focusing on households. Results Indirectly exposed group showed a higher prevalence of stunting (18% vs. 16.4%) than controls. Food safety was adequate in both groups (X 2 = 1.88, p = 0.597). The indirectly exposure children showed significantly higher calcium levels (9.99 ± 0.63 mg/dL) and significant increases in liver enzymes AST and GGT ( p < 0.001). ALP was 1.5 times lower than in unexposed children ( p < 0.001), showing a strong association with exposure time ( p = 0.009). The indirectly exposed group showed lower GH and IGF-1 levels; 2.55 and 1.28 times lower than in controls, respectively. Children with indirect exposure showed a significant reduction in AChE (7211 ± 1917 vs. 8368 ± 213 U/L, p < 0.001) and an even greater decrease in BChE (6426 ± 1664 vs. 8025 ± 1462 U/L, p < 0.001). Conclusion This work demonstrates an association between environmental exposure to organophosphate pesticides and children's growth and provides crucial insights for future research and policymaking.

Editorial: Advancing theory and application in Biological Invasions through hypothesis-driven science - Mariano A. Rodriguez-Cabal; Evangelina Schwindt; Laura A. Meyerson (Biological Invasions, 2026)

Introducing the new collection “Management Innovations and Insights” in Biological Invasions - Deah Lieurance; Evangelina Schwindt; Mariano A. Rodriguez-Cabal; Jasmin Packer; Laura A. Meyerson (Biological Invasions, 2026)

Governance Arrangements That Fit Social‐Ecological Context Are Associated With Fishery Sustainability - Mateja Nenadović; Alfredo Giron; Timothy Frawley; Adrian Munguia‐Vega; Kara E. Pellowe; Erica Ferrer; David Gill; Blanca González‐Mon; Andrew F. Johnson; Emilie Lindkvist; Fiorenza Micheli; Amy H. Weaver; et al. (Fish and Fisheries, 2026)
In many parts of the world, natural resources are primarily managed by governance arrangements at the local level. Those arrangements range from collective, such as cooperatives and associations, to individualistic, such as patrons and owner‐operators. A key question is how such arrangements influence resource use and associated social and ecological outcomes. We hypothesize that sustainable resource use is not associated with a specific governance arrangement, but instead that every type of arrangement has a certain set of social and ecological conditions under which sustainable resource use is feasible. This hypothesis was empirically investigated using fisheries landings data from Mexico. We found that sustainable resource use can be achieved through multiple governance arrangements provided that they are matched to appropriate social‐ecological contexts. Our findings help identify which governance arrangements are best suited to particular contexts and provide the initial building blocks for developing a theory of governance contextual fit in social‐ecological fishing systems.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Functional connectivity alterations in spinocerebellar ataxia type 10: insights from gray matter atrophy - Gustavo Padron-Rivera; Gabriel Ramirez‐Garcia; Amanda Chirino‐Perez; Angel Omar Romero-Molina; Adriana Ochoa-Morales; María Guadalupe Garcia-Gomar; Miguel Angel Ramirez‐Garcia; Omar Rodriguez-Mendoza; Diana Laura Torres-Vences; Birgitt Schüle; Erick Humberto Pasaye-Alcaraz; Carlos Roberto Hernandez-Castillo; et al. (Brain Imaging and Behavior, 2026)
Spinocerebellar ataxia type 10 (SCA10) is a rare, inherited neurological disease caused by an expansion of the non-coding ATTCT pentanucleotide repeat in the ATAXIN 10 gene. It is characterized by cerebellar ataxia and epilepsy. Previous research has demonstrated extensive white and gray matter degeneration, particularly in the cerebellum. However, the impact of the SCA10 mutation on functional connectivity (FC) remains unexplored. This study aimed to characterize intrinsic FC changes in SCA10 patients and their relationship to clinical manifestations. Structural and resting-state Magnetic Resonance Imaging (MRI) were obtained from 26 SCA10 patients and 26 control subjects. Voxel-based morphometry (VBM) and seed-ROI and Independent Components Analysis (ICA) were performed to identify cerebral atrophy and FC changes respectively. Additionally, correlation analyses were conducted between FC changes and scores from the Scale for the Assessment and Rating of Ataxia (SARA) and the Montreal Cognitive Assessment (MoCA). In SCA10 patients, VBM analysis revealed extensive gray matter loss in motor cortices and the cerebellum. FC analysis identified significant FC changes originating from seed-ROIs in the right cerebellar VI and left precentral gyrus. Furthermore, group comparison using ICA components showed that SCA10 patients exhibited higher FC in the sensorimotor and cerebellar functional networks. Moreover, the average Blood Oxygen Level Dependent (BOLD) signal within the cerebellar network negatively correlated with MoCA scores. In summary, SCA10 patients exhibited enhanced FC in brain regions that displayed gray matter atrophy, underscoring the impact of SCA10 degeneration on resting state networks and induction of potential maladaptive FC compensatory mechanisms.

Correction to: The Neuronal Ischemic Tolerance Is Conditioned by the Tp53 Arg72Pro Polymorphism - Maria E. Ramos-Araque; Cristina Rodriguez; Rebeca Vecino; Elisa Cortijo Garcia; Mercedes de Lera Alfonso; Mercedes Sanchez Barba; Laura Colàs-Campàs; Francisco Purroy; Juan F. Arenillas; Angeles Almeida; Maria Delgado-Esteban (Translational Stroke Research, 2026)

Correction to: Multiple exposure pathways to pesticide residues in tropical agroecosystems: A human health risk assessment in Costa Rica - José R. Montiel‑Mora; Greivin Perez‑Rojas; Laura Brenes‑Alfaro; Carlos E. Rodriguez‑Rodriguez (Environmental Monitoring and Assessment, 2026)

Nanoplastics internalization impairs mitochondrial activity in equine sperm - Sofia Dindo; Laura Tovar-Pascual; Vito Antonio Baldassarro; Diego Bucci; Beatrice Mislei; Marcella Spinaci; Jose Manuel Ortiz-Rodriguez (Theriogenology, 2026)

The effect of clay minerals on Li in martian groundwater simulant - Rachel Y. Sheppard; Jessica M. Weber; Laura E. Rodriguez; Cathy Trejo; Elisabeth M. Hausrath; Laura M. Barge (Icarus, 2026)

Associations between exposure to metals, chlorinated pesticides, and PCBs and differential leukocyte profiles in Flemish adolescents - Fen Zhang; Lützen Portengen; Hamid Y. Hassen; Laura Rodriguez Martin; Madeline Carsique; Amélie Crépet; Jasper Engel; Jacob Van Klaveren; Nicolas Van Larebeke; Willy Baeyens; Stefaan De Henauw; Tim S. Nawrot; et al. (Environmental Research, 2026)

Occupants’ willingness to share information for improved comfort and energy efficiency in offices - Marcel Schweiker; Dimitris Potoglou; Farah AlAtrash; Eleni Ampatzi; Maíra André; Elie Azar; Karol Bandurski; Leonidas Bourikas; Carolina Buonocore; Bin Cao; Giorgia Chinazzo; Rania Christoforou; et al. (Building and Environment, 2026)

Phytochemicals as promising agents against pathogenic free-living amoebas - Erick P. Gutiérrez-Grijalva; Laura A. Contreras-Angulo; Marilyn Shomara Criollo-Mendoza; J. Basilio Heredia; Jaime López-Cervantes; Dalia Isabel Sánchez-Machado; Jose Reyes Gonzalez-Galaviz; Libia Zulema Rodriguez-Anaya (Phytochemistry Reviews, 2026)

Effect of polystyrene nanoplastics on in vitro maturation of pig cumulus-encosed oocytes - Marcella Spinaci; Sofia Dindo; Nadia Govoni; Laura Tovar; Alessandro Marino Volsa; Cinzia Cappannari; Diego Bucci; Jose Manuel Ortiz-Rodriguez (Research in Veterinary Science, 2025)

Design, development and qualification of a european international berthing and docking mechanism (IBDM) - Joaquín Meléndez; Jeanette Bast; Johan Bogaerts; Jeremy Bouten; Angelo Costantino; Luc De Busser; Rutger De Nutte; Isabelle De Preter; Andy De Wilde; Felix De Wispelaere; Filip Dewitte; Wim Derkinderen; et al. (Journal of Space Safety Engineering, 2025)

Covalent organic framework-coated alumina for the removal of geosmin from water in recirculating aquaculture systems - Ana Vieira; Joana Araújo; Pablo Blanco Canella; Silvia Escudero-Curiel; Soraia P.S. Fernandes; Laura Rodriguez-Lorenzo; Juliana P.S. Sousa; Liliana P.L. Gonçalves; Salomé G.P. Soares; Marta Pazos; M. Ángeles Sanromán; Yury V. Kolen’ko; et al. (Journal of Environmental Chemical Engineering, 2025)

Integrative metabolomic and transcriptomic analysis reveals CYP450-driven biosynthesis of pentacyclic triterpene acids in Cecropia angustifolia - Juan E. Vivas-Moncayo; Paula C. Muñoz-Bonilla; Laura M. Rodriguez-Santa; Adrián C. Rodriguez-Ararat; Guillermo Montoya (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)
Pentacyclic triterpene acids (PTAs) are specialized plant metabolites known for their anti-inflammatory and antidiabetic preclinical reports. Cecropia angustifolia , a prominent species in the Andean montane forests, produces a variety of PTAs in its roots, but little is known about enzymes responsible for their oxidative structural decorations. In this study, we explored the biosynthetic route of PTAs oxidation by cytochrome P450 (P450s) enzymes, comparing wild-collected and in-vitro cultivated root tissues. Chemical profiling was carried out using targeted metabolomics to assess PTAs in both types of extracts. Oxidation patterns differed between the samples, suggesting distinct enzyme activity depending on growth conditions. To support these findings, we assembled a de novo transcriptome based on publicly available Cecropia RNA-seq data and predicted over 26,000 open reading frames. Four P450 families (CYP716A, CYP716C, CYP72A, and CYP71D) are potential contributors to triterpene oxidation, which were identified by homology-based annotation. Gene expression was examined by RT-qPCR, revealing differential transcriptional activity between wild and in-vitro roots. Nevertheless, these differences link the gene expression profile of P450s involved in this pathway to the TPAs metabolic expression. Notably, despite changes in expression, the capacity to generate oxidized PTAs was retained under both conditions. Our results indicate that the oxidative metabolism of triterpenes in C. angustifolia is largely conserved and responsive to environmental cues. This study enhances the current understanding of PTA biosynthesis and supports the use of in-vitro systems as a practical strategy to obtain valuable metabolites while minimizing ecological impact.

Linking genomic and proteomic signatures to brain amyloid burden: insights from GR@ACE/DEGESCO - Raquel Puerta; Itziar de Rojas; Pablo García-González; Clàudia Olivé; Oscar Sotolongo-Grau; Ainhoa García-Sánchez; Fernando García-Gutiérrez; Laura Montrreal; Juan Pablo Tartari; Ángela Sanabria; Vanesa Pytel; Carmen Lage; et al. (Functional & Integrative Genomics, 2025)

Oxidative environments promote the formation of detergent-resistant IgG aggregates mediated by Cu(II) assessed by optical density: implications in vivo - Christian Saporito-Magriña; Lila Lopez-Montañana; María Laura Facio; Guadalupe Pagano; Aldana Rodriguez; Juan Ignacio Bellida; Marisa Gabriela Repetto (JBIC Journal of Biological Inorganic Chemistry, 2025)

β-carotene nanoemulsions co-ingested with oatmeal of different viscosities: a semi-dynamic in vitro digestion approach - Anali Parsi; Anna Molet-Rodriguez; Olga Martín-Belloso; Laura Salvia-Trujillo (Food Research International, 2025)

Validation of pharmacokinetic model for quizartinib quantified by UPLC-MS/MS in patients with FLT3-ITD negative newly diagnosed acute myeloid leukemia - Antonio Solana-Altabella; Carles Iniesta-Navalón; Maria Chovi-Trull; Rebeca Rodriguez-Veiga; Marina Lopez-Nogueroles; David Martínez-Cuadrón; Mayte Gil-Candel; Laura Torres-Miñana; Evelyn Acuña-Cruz; Isabel Cano-Ferri; Blanca Boluda; Irene Navarro-Vicente; et al. (European Journal of Clinical Pharmacology, 2025)
Purpose Quizartinib pharmacokinetics in FLT3-ITD negative acute myeloid leukemia (AML) remain largely unexplored. This study aims to validate a population pharmacokinetics model (popPK) for quizartinib in plasma samples of FLT3-ITD negative AML patients. To do so, an ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) method has been developed and validated for the quantification of quizartinib. Methods Plasma samples were collected from FLT3-ITD negative newly diagnosed AML patients undergoing quizartinib therapy at induction in the QUIWI phase II clinical trial [NCT04107727, PETHEMA group] between March 2020 and February 2022. The UPLC-MS/MS method was developed and validated. A previously described popPK model was validated using external validation techniques and implemented using the software NONMEM v7.5. Results The developed UPLC-MS/MS method demonstrated high accuracy and precision with a linear range of 6 to 200 ng/mL, with relative standard deviation between 3–11 and accuracy of 88–97% from nominal values. The external validation of the quizartinib popPK model showed minimal bias at the population level (MdPE: -9.86%; ME: 0.50 ng/mL, p = 0.964), but moderate imprecision (MdAPE: 32.28%) and suboptimal accuracy (F20: 24.5%; F30: 43.4%). Individual predictions improved performance, with negligible bias (MdPE: -0.50%), acceptable precision (MdAPE: 11.27%), and F20 (64.2%) and F30 (77.4%) exceeding predefined thresholds. Visual predictive checks confirmed adequate prediction of median concentrations, though some deviations occurred at extremes. Conclusion This study presents a replicable UPLC-MS/MS method for the determination of quizartinib in plasma. The validated popPK model can be used to optimize dosing strategies in future clinical studies.

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Evaluation of the efficacy of polymeric antigen BLSOmp31 formulated in a new cage-like particle adjuvant (ISPA YOLK) administered by parenteral or mucosal routes against Brucella ovis in rams - María Celeste Moran; Agostina Tammone Santos; Paula Dominguez; Lucila Moriones; María Victoria Nieto Farias; Laura Maté; Juan Agustín García; Tobias Kuhn; Fernando Alberto Paolicchi; María Andrea Fiorentino; Marcelo Gastón Rodriguez; Jorge Pablo García; et al. (Veterinary Immunology and Immunopathology, 2025)

Influence of intensified upwelling on two different Corallina officinalis Linneo 1758 populations by exploring direct and indirect effects - Eva Rothäusler; Laura Ramajo; Lilly-Mo Kuhn; Fadia Tala; Alejandro B. Rodriguez-Navarro; Constanza Mena; Jorge Inostroza (Marine Environmental Research, 2025)

Evaluating the role of physical mechanisms as possible triggers for turbidity currents in a deep ocean seamount - Susana M. Lebreiro; Álvaro Peliz; Laura Antón; Sílvia Nave; M. Isabel Reguera; Rocío Lozano-Luz; Claire Waelbroeck; Simon Crowhurst; Belen Martrat; Jordi F. Lopez; Raphaël Hebert; Alejandra Lopez-Rodriguez (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

The Bermuda Triangle of paediatric brain cancers: epigenetics, developmental timing window and cell of origin - Afraah Cassim; Yolanda Colino-Sanguino; Sarah L. Fox; Laura Rodriguez de la Fuente; Hannah E. Hartley; Fatima Valdes-Mora (Cancer and Metastasis Reviews, 2025)
Paediatric brain cancers are aggressive tumours that urgently need deeper understanding of their cellular and molecular vulnerabilities to facilitate the development of effective treatments. These tumours frequently arise from epigenetic alterations in specific immature cell states of the developing prenatal or neonatal brain. In this review, we propose a “three-event” model composed of an epigenetic event, developmental timing window and the cell of origin for tumour initiation in paediatric brain tumours. We focus on three types of paediatric gliomas: diffuse midline gliomas (DMG), diffuse hemispheric gliomas (DHG) and posterior fossa A ependymomas (PFA-EPN), which reflect our proposed three-event model. Additionally, we discuss the methods and models used to study these three events separately or simultaneously. Taken together, this review highlights the spatio-temporal vulnerable cell states during brain development and which molecular drivers hijack these cues to induce cell state stalling and tumour initiation. The next steps to expand our understanding of the order of events and their use in therapy are further discussed.

Enhancing data interoperability in human biomonitoring studies: the HBM data toolkit - Ruben Peeters; Laura Rodriguez Martin; Fen Zhang; Hanny Willems; Liese Gilles; Jan Theunis; Jos Bessems; Caio Mescouto Terra de Souza; Stijn Baken; Dirk Devriendt; Eva Govarts (International Journal of Hygiene and Environmental Health, 2025)

A machine learning approach for type 2 diabetes diagnosis and prognosis using tailored heterogeneous feature subsets - J. Ramón Navarro-Cerdán; Pedro Pons-Suñer; Laura Arnal; Joaquim Arlandis; Rafael Llobet; Juan-Carlos Perez-Cortes; Francisco Lara-Hernández; Celeste Moya-Valera; Maria Elena Quiroz-Rodriguez; Gemma Rojo-Martinez; Sergio Valdés; Eduard Montanya; et al. (Medical & Biological Engineering & Computing, 2025)
Type 2 diabetes (T2D) is becoming one of the leading health problems in Western societies, diminishing quality of life and consuming a significant share of healthcare resources. This study presents machine learning models for T2D diagnosis and prognosis, developed using heterogeneous data from a Spanish population dataset (Di@bet.es study). The models were trained exclusively on individuals classified as controls and undiagnosed diabetics, ensuring that the results are not influenced by treatment effects or behavioral changes due to disease awareness. Two data domains are considered: environmental (patient lifestyle questionnaires and measurements) and clinical (biochemical and anthropometric measurements). The preprocessing pipeline consists of four key steps: geospatial data extraction, feature engineering, missing data imputation, and quasi-constancy filtering. Two working scenarios (Environmental and Healthcare) are defined based on the features used, and applied to two targets (diagnosis and prognosis), resulting in four distinct models. The feature subsets that best predict the target have been identified based on permutation importance and sequential backward selection, reducing the number of features and, consequently, the cost of predictions. In the Environmental scenario, models achieved an AUROC of 0.86 for diagnosis and 0.82 for prognosis. The Healthcare scenario performed better, with an AUROC of 0.96 for diagnosis and 0.88 for prognosis. A partial dependence analysis of the most relevant features is also presented. An online demo page showcasing the Environmental and Healthcare T2D prognosis models is available upon request. Graphic abstract

Wood formation mechanisms of Cedrela fissilis Vell. in extreme years: Climatic, anatomical and chemical predictors - Daigard Ricardo Ortega-Rodriguez; Andrea Hevia; Gabriela Morais Olmedo; Bruna Hornink; Fidel A. Roig; Mario Tomazello-Filho; Raúl Sánchez-Salguero; Luiz Santini; Laura Yáñez-Espinosa (Dendrochronologia, 2025)

SEC Injectable Solution Preserves Activated T Cells in Hypothermic Condition - Anthony Maino; Olivier Manches; Laura Rodriguez; Zoran Ivanovic; Ramiro Gisler; Philippe Saas; Laurence Chaperot (Stem Cell Reviews and Reports, 2025)

Deregulated mRNA and microRNA Expression Patterns in the Prefrontal Cortex of the BTBR Mouse Model of Autism - Catherine Mooney; Andrea Parlante; Giulia Canarutto; Andrea Grigoli; Maria Luisa Scattoni; Laura Ricceri; Eva Maria Jimenez-Mateos; Amaya Sanz-Rodriguez; Elena Clementi; Silvano Piazza; David C. Henshall; Giovanni Provenzano (Molecular Neurobiology, 2025)
Autism spectrum disorder (ASD) is a neurodevelopmental condition caused by both genetic and environmental factors. Since no single gene variant accounts for more than 1% of the cases, the converging actions of ASD-related genes and other factors, including microRNAs (miRNAs), may contribute to ASD pathogenesis. To date, few studies have simultaneously investigated the mRNA and miRNA profiles in an ASD-relevant model. The BTBR mouse strain displays a range of behaviors with ASD-like features but little is known about the protein-coding and noncoding gene expression landscape that may underlie the ASD-like phenotype. Here we performed parallel mRNA and miRNA profiling using the prefrontal cortex (PFC) of BTBR and C57BL/6 J (B6) mice. This identified 1063 differentially expressed genes and 48 differentially expressed miRNAs. Integration of mRNA and miRNA data identified a strong inverse relationship between upregulated (DEGs) and downregulated miRNAs, and vice versa. Pathway analysis, taking account of the inverse relationship between differentially expressed miRNAs and their target mRNAs highlighted significant shared enrichment in immune signaling, myelination, and neurodevelopmental processes. Notably, miRNA changes were predicted to affect synapse-related functions but we did not find enrichment of protein-coding genes linked to cellular components or biological processes related to synapses in the PFC of BTBR mice, indicating processes may evade miRNA control. In contrast, other miRNAs were predicted to have extensive relationships with DEGs suggesting their role as potential hub coordinators of gene expression. Profiling findings were confirmed via qRT-PCR for representative protein-coding transcripts and miRNAs. Our study underscores the complex interplay between gene expression and miRNA regulation within immune and inflammatory pathways in the BTBR model, offering insights into the neurodevelopmental mechanisms of ASD. These results support the value of the BTBR mouse model and identify strategies that could adjust molecular pathways for therapeutic applications in ASD research.

Active and passive pathways of nutrient transfer in coral reef ecosystems - Ruth E. Dunn; Nicholas A. J. Graham; Laura-Li Jeannot; Rucha Karkarey; F. Javier Gonzalez-Barrios; Ines D. Lange; Julia Rodriguez Fillol; Ronan Roche; Marleen Stuhr; Cassandra E. Benkwitt (Coral Reefs, 2025)
Coral reefs receive both passive and active nutrient subsidies, supplied via oceanographic processes and animal-mediated transfer, which can bolster reef productivity and resilience to disturbance. We examined the relative importance of these two pathways across lagoonal and seaward reefs, reefs of different depths, and those around islands either with or without breeding seabird colonies using carbon and nitrogen stable isotopes (ð 13 C and ð 15 N) and nutrient metrics (per cent N, %N and carbon-to-nitrogen ratios, C:N). We found increased passive oceanic nutrient inputs in reefs that were both deep and seaward facing, indicated by lower ð 13 C values. Enriched ð 15 N values and lower carbon-to-nitrogen ratios within reefs adjacent to islands with seabird colonies provided evidence of the role of seabirds as active vectors of nutrients to coral reef food webs, particularly within shallow, lagoonal reefs. Though %N values did not seem to provide a good indicator through which to disentangle active vs passive nutrient transport within this context, variation in ð 13 C and ð 15 N values and C:N ratios highlighted the interplay between passive oceanic processes and active seabird contributions to coral reefs. We emphasise the importance of both preserving and restoring natural nutrient pathways, particularly at a time when coral reef ecosystems are under increasing pressure from anthropogenic threats.

The effect of non-optimal ambient temperature on daily mortality in Colombia 2010–2019 - Nicolas Borchers-Arriagada; Antonio Gasparrini; Laura A. Rodriguez-Villamizar (Air Quality, Atmosphere & Health, 2025)
Adverse effects of non-optimal temperatures on mortality have been reported in different climates. However, only a low number of studies have been conducted in tropical locations where these effects might differ. Here, we estimate the association between ambient air temperature and all-cause mortality and assess the impact of non-optimal temperatures on attributable mortality at national and subnational levels in Colombia during 2010–2019. We obtained daily temperature and mortality data for 32 departments and conducted a two-stage analysis. In stage-1 we fitted a time-series Poisson model for each department and estimated the mortality-temperature association using distributed-lag-nonlinear models with 7–28 days of lag. In stage-2, we pooled these estimates using a multivariate meta-analytic model including mean temperature, relative humidity, and a multidimensional poverty index. We calculated attributable deaths and fractions due to non-optimal temperatures and due to overall heat and cold. We analyzed 2,561,561 deaths and found marked differences in exposure–response curves of mortality-temperature, where most departments showed acute heat effects but no cold effects for the 7-days lag. This lag-response curve for heat showed that the risk of death is higher during the same day (lag 0) of extreme temperatures and decreases after the third day. The country attributable fraction due to non-optimal temperature was higher for heat (1.77, 95% CI 1.16 – 2.31) during the 0–7 days lag, but higher for cold temperatures (4.68, 95% CI 2.34 – 6.72) during the 0–28 days lag. There was high heterogeneity in the estimated risks between departments. These results should inform planning adaptation strategies for climate change differentiated at subnational level.

Focused high-protein supplementation to ewes grazing Campos grassland during mid gestation improves maternal-fetal blood flow and skeletal muscle mass of the progeny - Javier Ithurralde; Ana Inés Trujillo; Ana Laura Astessiano; Mariana Garcia Kako Rodriguez; Ezequiel Jorge-Smeding; Danilo Fila; Carlos Batista; Alejandro Bielli; Raquel Pérez-Clariget (Livestock Science, 2025)

Consequential life cycle assessment of pretreatment strategies for a microalgae-based wastewater treatment pilot unit in a circular livestock industry bioeconomy - Anaid López-Sánchez; Carlos Daniel García-López; Gary Ossmar Lara-Topete; Juan Daniel Castanier-Rivas; Paloma Barajas-Álvarez; Martín Esteban González-López; Ana Laura Silva-Gálvez; Hongying Zhou; Christopher Q. Lan; Carlos Eduardo Robles-Rodriguez; Samir Meramo-Hurtado; Misael Sebastián Gradilla-Hernández (Algal Research, 2025)

Amino acid and acylcarnitine profile of Aedes aegypti (L) post-blood feeding, after permethrin exposure, and during the life cycle - Mariana Lizbeth Jiménez-Martínez; Gerardo de Jesús Trujillo-Rodriguez; María de Lourdes Ramírez-Ahuja; Olga Karina Villanueva-Segura; Patricio Adrián Zapata-Morin; Griffith Samuel Lizarraga; Laura E. Martinez-de-Villarreal; Margarita L. Martinez-Fierro; Ivan Delgado-Enciso; Jose Ignacio Gonzalez-Rojas; Adriana E. Flores; Antonio Guzman-Velasco; et al. (Insect Biochemistry and Molecular Biology, 2025)

Wastewater treatment and energy generation for dark fermentation bioreactor: preliminary results - Laura Estefania Vanegas; Lucia Andrea Hurtado; Karol Lucia Fuentes; Mario Alberto Escobar; Tatiana Rodriguez Chaparro (International Journal of Environmental Science and Technology, 2025)
H 2 is known as the main energy vector in the global energy transition. However, the use of fossil fuels for its production remains the most widely used primary source. Among the new alternatives for the organic production of H 2 , the Dark Fermentation process is an attractive technique since the raw material is residual biomass. H 2 is currently used for transport and fertilizer production. Hence, this study aims to evaluate the feasibility of producing electricity from H 2 produced in a Dark Fermentation process by treating synthetic wastewater in a packed bed bioreactor coupled with a fuel cell. The results showed that the maximum H 2 production rate and H 2 yield were 108 mL H 2 /h.L and 10.57 mol H 2 / mol, respectively; the maximal current value was ca. 13.7 mA for an active electrode area of 10 cm 2 ; and the higher tension was 1.3. Moreover, the Fuel Cell generated an average current of 3.12 mA for 55 h with a voltage of 210 mV. It can be concluded that dark fermentation promotes electricity generation. However, it is still necessary to develop storage techniques for H 2 to maintain the electricity generated continuously. Graphical abstract

Larval chaetotaxy and morphometry of Coelostomatini and Sphaeridiini (Coleoptera: Hydrophilidae): Insights into terrestrial adaptations of Dactylosternum Wollaston, Hydroglobus Knisch, and Sphaeridium Fabricius - Georgina Rodriguez; Miguel Archangelsky; Patricia Laura María Torres (Zoologischer Anzeiger, 2025)

Sustainability in urban agriculture: The role of biochar in enhancing the productive capacity of compost-based growing media for rooftop farming - Giuseppe Picca; Asier Goñi-Urtiaga; Laura Lozano de Sosa; Maria Victoria Colombo Rodriguez; Isabel Fernández Navarro; César Plaza; Marco Panettieri (Urban Forestry & Urban Greening, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Nutritional ketosis modulates the methylation of cancer-related genes in patients with obesity and in breast cancer cells - Paula M Lorenzo; Andrea G Izquierdo; Gemma Rodriguez-Carnero; Nicolas Costa-Fraga; Angel Díaz-Lagares; Cristina Porca; Daniel de Luis; Cristina Tejera; Laura De Paz; Juan Cueva; Diego Bellido; Ana B Crujeiras (Journal of Physiology and Biochemistry, 2025)
Scientific evidence demonstrates that a very low-calorie ketogenic diet (VLCKD) is effective and beneficial in the treatment of obesity, capable of reversing the methylome associated with obesity and has immunomodulatory capacity. This effect is in part promoted by nutritional ketosis and could be involved in counteracting obesity-related cancer. The aim of this study was to evaluate the effect of nutritional ketosis on the methylation of genes related to tumor processes in patients with obesity and in breast cancer cells. Based on methylome data (Infinium MethylationEPIC BeadChip, Illumina) from patients with obesity treated with a VLCKD for weight loss ( n = 10; n = 5 women, age = 48.8 ± 9.20 years, BMI = 32.9 ± 1.4 kg/m2), genes belonging to cancer-related pathways were specifically evaluated and further validated in vitro in MDA-MB-231 (triple negative) and MCF7 (RE positive) breast tumor cells pretreated for 72 h with βOHB, the main ketone body, secretome from visceral (VATs) or subcutaneous (SATs) adipose tissue of patients with obesity. The cell tumoral phenotype was evaluated by proliferation assay and expression of cancer-related genes. VLCKD-induced nutritional ketosis promoted changes in the methylation of 18 genes (20 CpGs; 17 hypomethylated, 3 hypermethylated) belonged to cancer-related pathways with MAPK10, CCN1, CTNNA2, LAMC3 and GLI2 being the most representative genes. A similar pattern was observed in the MDA-MB-231 cells treated with β-OHB, without changes in MCF7. These epigenetic changes paralleled the tumoral phenotype modulated by the treatments. Taking together these results highlight the potential role of VLCKD as an adjuvant to anticancer treatment in groups more susceptible to the development of cancer such as patients with obesity, exerting epigenetic regulation through nutritional ketosis and weight loss.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Platelet Analysis in the Thrombus Plus Serum BNP for Detecting Clot-Related Atrial Fibrillation. Results From the ITACAT Multicentric Registry - Jorge Pagola; Jesus Juega; Laura Dorado; Maria Hernandez-Perez; Carlos Lazaro; Alvaro Garcia-Tornel; Marta Olive; Manuel Requena; Marta Rubiera; Marian Muchada; Noelia Rodriguez-Villatoro; David Rodriguez-Luna; et al. (Translational Stroke Research, 2025)

Temperature Drives Seagrass Recovery Across the Western North Atlantic - Fee O. H. Smulders; Justin E. Campbell; Andrew H. Altieri; Anna R. Armitage; Elisabeth S. Bakker; Savanna C. Barry; S. Tatiana Becker; Enrique Bethel; James G. Douglass; Hannah J. van Duijnhoven; Jimmy de Fouw; Thomas K. Frazer; et al. (Global Change Biology, 2025)
Climate‐driven shifts in herbivores, temperature, and nutrient runoff threaten coastal ecosystem resilience. However, ecological resilience, particularly for foundation species, remains poorly understood due to the scarcity of field experiments conducted across appropriate spatial and temporal scales that investigate multiple stressors. This study evaluates the resilience of a widespread tropical marine plant (turtlegrass) to disturbances across its geographic range and examines how environmental gradients in (a)biotic factors influence recovery. We assessed turtlegrass resilience by following recovery rates for a year after a simulated pulse disturbance (complete above‐ and belowground biomass removal). Contrary to studies in temperate areas, higher temperature generally enhanced seagrass recovery. While nutrients had minimal individual effects, they reduced aboveground recovery when combined with high levels of herbivore grazing (meso and megaherbivore). Belowground recovery was also affected by combined high levels of nutrients and grazing (megaherbivores only). Light availability had minimal effects. Our results suggest that the resilience of some tropical species, particularly in cooler subtropical waters, may initially benefit from warming. However, continuing shifts in nutrient supply and changes in grazing pressure may ultimately serve to compromise seagrass recovery.

Fosfomycin in bacteraemic urinary tract infection due to multidrug-resistant Escherichia coli : insights of post hoc DOOR analysis of the FOREST trial - Jesús Sojo-Dorado; Inmaculada López-Hernández; Belén Gutiérrez-Gutiérrez; Sandra De la Rosa-Riestra; Fernando Docobo-Pérez; Alicia Hernánez-Torres; Álvaro Pascual; Jesús Rodriguez-Baño; Esperanza Merino de Lucas; Laura Escolà-Vergé; Elena Bereciartua; Elisa García-Vázquez; et al. (Infectious Diseases, 2025)

Updated Terminology for the Nutrition and Dietetics Profession: A Comprehensive Revision to the Commission on Dietetic Registration’s Definition of Terms List - Chris Messenger; Nancy Walters; Anna Marie Rodriguez; Laura Gollins; ShLanda Rochel Burton; Lini Alappat; Rayna McCann; Michelle Strang; Dana Buelsing Sowards; Carol Gilmore; Karen Hui (Journal of the Academy of Nutrition and Dietetics, 2025)

Sources, levels, and determinants of indoor air pollutants in Europe: A systematic review - Carla Martins; Vânia Teófilo; Marta Clemente; Mariana Corda; Jose Fermoso; Alicia Aguado; Sandra Rodriguez; Hanns Moshammer; Alexandra Kristian; Mireia Ferri; Belén Costa-Ruiz; Leticia Pérez; et al. (Science of The Total Environment, 2025)

Gluconacetobacter diazotrophicus triggers ISR involving SA and JA/Et defense-related pathways to respond against Ralstonia solanacearum in Arabidopsis and optimizes the cellular redox state maintaining reduced FITNESS levels - María Sol Srebot; María Belén Ripa; Julieta Andrea Gallozo; Gabriel Roberto Bettucci; Matías Damián Ferretti; Luciano David D´Attilio; María Laura Martínez; Elena Graciela Orellano; María Victoria Rodriguez (Plant and Soil, 2025)

An Injectable Solution for Preservation of Hematopoietic Stem and Progenitors Cells in Hypothermic Condition - Jean Chevaleyre; Laura Rodriguez; Esther Attebi; Pascale Duchez; Zoran Ivanovic (Stem Cell Reviews and Reports, 2025)

Preliminary insights into Red LED Irradiation for thawing cryopreserved boar semen - Laura Tovar; Diego Bucci; Marcella Spinaci; Ludovica Mammi; Barbara Merlo; Joan Enric Rodriguez Gil; José Manuel Ortiz Rodriguez (Animal Reproduction Science, 2025)

Between and within-city variations of PM2.5 oxidative potential in five cities in Colombia - Néstor Y. Rojas; Dayana M. Agudelo-Castañeda; Daniela Bustos; Krystal J. Godri Pollitt; Dong Gao; Laura A. Rodriguez-Villamizar (Air Quality, Atmosphere & Health, 2025)
Fine particulate matter (PM 2.5 ) has been shown to cause oxidative stress, which has negative health consequences. The oxidative potential (OP) of PM 2.5 , a promising health exposure metric, was assessed in five Colombian cities using the synthetic respiratory tract lining fluid assay that tracks the depletions of glutathione and ascorbate. For this, a set of 91 integrated 2-week ambient PM 2.5 samples were collected using Ultrasonic Personal Aerosol Samplers (UPAS) at background (5), traffic (37), industrial (12) and residential (37) sites. Across all site types, mean PM 2.5 mass concentration was 20.20 ± 9.36 µg m − 3 . The oxidative potential (OP AA for ascorbate and OP GSH for glutathione) varied widely across cities with an average of 2.67 ± 1.27 for AA and 2.93 ± 1.22 % depletion m − 3 for GSH. OP metrics among cities were not correlated with PM 2.5 mass concentrations. Overall, industrial sites showed higher PM 2.5 mass concentrations and OP AA . In contrast, OP GSH was not found to differ among industrial, traffic, or residential sites, but was lower for background sites. Our findings provide substantial evidence of variations in PM 2.5 OP between cities and within the cities. Further research is needed to assess the association between OP and adverse health effects, as well as to attribute the sources that cause such variations.

Molecular interplay of symbiotic and defensive responses in the non-model legume Arachis hypogaea - Johan Rodriguez; María Laura Tonelli; Adriana Fabra; Fernando Ibañez (Symbiosis, 2024)

Analysis of stallion spermatozoa metabolism using Agilent Seahorse XFp Technology - Jose Manuel Ortiz-Rodriguez; Diego Bucci; Laura Tovar-Pascual; Silvia Granata; Marcella Spinaci; Salvatore Nesci (Animal Reproduction Science, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Bioaccumulation, biodistribution, and transformation of polyvinylpyrrolidone-coated silver nanoparticles in edible seaweeds - Monica Quarato; Laura Rodriguez-Lorenzo; Ivone Pinheiro; Juan José López-Mayán; Mick Mackey; Antonio Moreda-Piñeiro; Miguel Spuch-Calvar; Julie Maguire; Pilar Bermejo-Barrera; Miguel A. Correa-Duarte; Begoña Espiña (Science of The Total Environment, 2024)

Pilot scale on-site demonstration and seasonality assessment of nitrogen recovery and water reclamation from pig's slurry liquid fraction - Ruben Rodriguez-Alegre; Julia Zapata-Jimenez; Laura Perez Megias; Carlos Andecochea Saiz; Sonia Sanchis; Montserrat Perez-Moya; Julia Garcia-Montano; Xialei You (Journal of Environmental Management, 2024)

Increasing climate-related resilience in the forest-based value chains? A policy perspective - Alice Ludvig; Blasius Schmid; Barbara Öllerer; Laura Nikinmaa; Pilar Hurtado; Montserrat Rodriguez-Ogea; Anne Toppinen (Forest Policy and Economics, 2024)

Diving into the metabolic interactions of titanium dioxide nanoparticles in “Sparus aurata” and “Ruditapes philippinarum” - Mário Jorge Araújo; María Vazquez; Laura Rodriguez-Lorenzo; Antonio Moreda-Piñeiro; Elza Fonseca; Natalia Mallo; Ivone Pinheiro; Monica Quarato; Elizabeth Bigorra-Ferré; Ana Matos; Aldo Barreiro-Felpeto; Maria V. Turkina; et al. (Environmental Pollution, 2024)

Cardiac alterations induced by Heloderma horridum horridum venom in rats: An experimental study with ECG analysis using a linear regression algorithm - Karla Isabel Vazquez-Gonzalez; Alberto Ochoa-Brust; Alejandrina Rodriguez-Hernandez; Hugo Ventura-Cisneros; Gisela Jareth Lino-Lopez; Rafael Barbosa-Valdovinos; Armando Rodriguez-Vazquez; Oscar F. Vazquez-Vuelvas; Ramon A. Felix; Juana M. Jiménez-Vargas; Valery Melnikov; Laura Leticia Valdez-Velazquez (Toxicon, 2024)

Trajectory, fate, and magnitude of continental microplastic loads to the inner shelf: A case study of the world's largest coastal shallow lagoon - Carolina Rodriguez; Pablo Silva; Laura Moreira; Larissa Zacher; Andreia Fernandes; Remi Bouyssou; Isabel Jalón-Rojas; Osmar Moller; Felipe Garcia-Rodriguez; Grasiela Lopes Leães Pinho; Elisa Fernandes (Science of The Total Environment, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Chromatographic enantioresolution and stereochemical characterization of synthetic cannabinoid receptor agonists with Whelk-O®1 chiral stationary phases under mass spectrometry compatible reversed-phase conditions: A study case with seized samples - Ina Varfaj; Michele Protti; Alessandro Di Michele; Jose Gonzalez-Rodriguez; Andrea Carotti; Roccaldo Sardella; Laura Mercolini (Analytica Chimica Acta, 2024)

Detection of submicron- and nanoplastics spiked in environmental fresh- and saltwater with Raman spectroscopy - Jessica Caldwell; Laura Rodriguez-Lorenzo; Begoña Espiña; Aaron Beck; Friederike Stock; Kathrin Voges; Katsia Pabortsava; Christopher Feltham; Alice Horton; Richard Lampitt; Barbara Rothen-Rutishauser; Patricia Taladriz-Blanco; et al. (Marine Pollution Bulletin, 2024)

Pharmacokinetics and safety of LEAD-452, an EGFR-specific 4-1BB-agonistic trimerbody in non-human primates - Rocío Navarro; Susana Frago; Oana Hangiu; Ainhoa Erce-Llamazares; Rodrigo Lázaro-Gorines; Miguel A. Morcillo; José L. Rodriguez-Peralto; Laura Sanz; Marta Compte; Luis Alvarez-Vallina (Toxicology and Applied Pharmacology, 2024)

The oldest fossil hominin from Italy: Reassessment of the femoral diaphysis from Venosa-Notarchirico in its Acheulean context - Ileana Micarelli; Simona Minozzi; Laura Rodriguez; Fabio di Vincenzo; Rebeca García-González; Valentina Giuffra; Robert R. Paine; José-Miguel Carretero; Gino Fornaciari; Marie-Hélène Moncel; Giorgio Manzi (Quaternary Science Reviews, 2024)

Training Promotoras to Implement a Mindfulness-Based Healthy Lifestyle Program in Rural Communities - Sandra Soca Lozano; Acadia W. Buro; Karen Gonzalez-Videla; Carmen Rodriguez; Diana Rancourt; Heewon L. Gray; Rocio Bailey; Laura Redwine; Marilyn Stern (Journal of Nutrition Education and Behavior, 2024)

Phthalates and substitute plasticizers: Main achievements from the European human biomonitoring initiative HBM4EU - Antje Gerofke; Rosa Lange; Nina Vogel; Phillipp Schmidt; Till Weber; Madlen David; Hanne Frederiksen; Kirsten Baken; Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Žanna Martinsone; et al. (International Journal of Hygiene and Environmental Health, 2024)

Crouzon syndrome with kleeblattschädel skull - Angela Patricia Guarnizo Capera; Laura Andrea Campaña Perilla; Maria Alejandra Rueda; José David Cardona Ortegón; Gustavo Adolfo Triana Rodriguez (Acta Neurologica Belgica, 2024)

Residential surrounding greenness and the incidence of childhood asthma: Findings from a population-based cohort in Ontario, Canada - Razieh Mansouri; Eric Lavigne; Robert Talarico; Audrey Smargiassi; Laura A. Rodriguez-Villamizar; Paul J. Villeneuve (Environmental Research, 2024)

Development of Catharanthus callus cell lines for indole-derived alkaloids production - Daniel Arturo Zavala-Ortiz; María Ines Infanzón-Rodríguez; Javier Gomez-Rodriguez; Diana Laura Palacios-Pérez; Carlos Augusto Ledesma-Escobar; María Guadalupe Aguilar-Uscanga (South African Journal of Botany, 2024)

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

New versus naturally aged greenhouse cover films: Degradation and micro-nanoplastics characterization under sunlight exposure - Carmen Sorasan; Patricia Taladriz-Blanco; Laura Rodriguez-Lorenzo; Begoña Espiña; Roberto Rosal (Science of The Total Environment, 2024)

Neighborhood greenness and participation in specific types of recreational physical activities in the Sister Study - Laura A. Rodriguez-Villamizar; Kim Hellemans; Michael Jerrett; Jason Su; Dale P. Sandler; Paul J. Villeneuve (Environmental Research, 2024)

Andean soil-derived lignocellulolytic bacterial consortium as a source of novel taxa and putative plastic-active enzymes - Laura Díaz-García; Maria Chuvochina; Golo Feuerriegel; Boyke Bunk; Cathrin Spröer; Wolfgang R. Streit; Luis M. Rodriguez-R; Jörg Overmann; Diego Javier Jiménez (Systematic and Applied Microbiology, 2024)

Intra-urban variability of long-term exposure to PM2.5 and NO2 in five cities in Colombia - Laura A. Rodriguez-Villamizar; Yurley Rojas; Sara Grisales; Sonia C. Mangones; Jhon J. Cáceres; Dayana M. Agudelo-Castañeda; Víctor Herrera; Diana Marín; Juan G. Piñeros Jiménez; Luis C. Belalcázar-Ceron; Oscar Alberto Rojas-Sánchez; Jonathan Ochoa Villegas; et al. (Environmental Science and Pollution Research, 2023)
Rapidly urbanizing cities in Latin America experience high levels of air pollution which are known risk factors for population health. However, the estimates of long-term exposure to air pollution are scarce in the region. We developed intraurban land use regression (LUR) models to map long-term exposure to fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the five largest cities in Colombia. We conducted air pollution measurement campaigns using gravimetric PM 2.5 and passive NO 2 sensors for 2 weeks during both the dry and rainy seasons in 2021 in the cities of Barranquilla, Bucaramanga, Bogotá, Cali, and Medellín, and combined these data with geospatial and meteorological variables. Annual models were developed using multivariable spatial regression models. The city annual PM 2.5 mean concentrations measured ranged between 12.32 and 15.99 µg/m 3 while NO 2 concentrations ranged between 24.92 and 49.15 µg/m 3 . The PM 2.5 annual models explained 82% of the variance ( R 2 ) in Medellín, 77% in Bucaramanga, 73% in Barranquilla, 70% in Cali, and 44% in Bogotá. The NO 2 models explained 65% of the variance in Bucaramanga, 57% in Medellín, 44% in Cali, 40% in Bogotá, and 30% in Barranquilla. Most of the predictor variables included in the models were a combination of specific land use characteristics and roadway variables. Cross-validation suggests that PM 2.5 outperformed NO 2 models. The developed models can be used as exposure estimate in epidemiological studies, as input in hybrid models to improve personal exposure assessment, and for policy evaluation.

Trauma-Informed Care Training for Dietetic Interns Improves Attitudes Toward Women Who Have Experienced Trauma - Nancy Rodriguez; Diana M. Gonzales-Pacheco; Laura D. Byham-Gray; Pamela Rothpletz-Puglia (Journal of Nutrition Education and Behavior, 2023)

Assessment of physicochemical parameters in argentinian Yerba Mate: Variability among different commercial brands - Sofía Baldor; Daniela del Rosario Venica; Laura Cardozo; Lucía Bértolo; María Gianina Bottero; Lucía Rodriguez-Livov; Aldana Giudici; Valeriana Diani; Débora Natalia López; Micaela Galante; Darío Spelzini; María Laura Pedrido; et al. (Food and Humanity, 2023)

Why are you hitting yourself? Whole-exome sequencing diagnosis of monogenic autoimmunity - Lina M. Castano-Jaramillo; Francisco Rivas Larrauri; Selma C. Scheffler-Mendoza; Alonso Gutierrez-Hernandez; Juan Carlos Bustamante Ogando; Paulina Colin; Margarita Ortega Cisneros; Sandra Rajme-López; Edgar Alejandro Medina-Torres; Laura Berron Ruiz; Ana Luisa Rodriguez-Lozano; Sara Elva Espinosa Padilla; et al. (Journal of Genetics, 2023)

Geological context and human exposures to element mixtures in mining and agricultural settings in Colombia - Oscar Florez-Vargas; Eugenio Vilanova; Carolina Alcaide; José A. Henao; Carlos A. Villarreal-Jaimes; Olga M. Medina-Pérez; Laura A. Rodriguez-Villamizar; Alvaro J. Idrovo; Luz H. Sánchez-Rodríguez (Science of The Total Environment, 2023)

Effect of stabilization time and soil chromium concentration on Sesbania virgata growth and metal tolerance - Natalia Rodriguez; Sofía Carusso; Ángela Juárez; Yanina El Kassisse; Valeria Rodriguez Salemi; Laura de Cabo (Journal of Environmental Management, 2023)

Getting fat and stressed: Effects of dietary intake of titanium dioxide nanoparticles in the liver of turbot Scophthalmus maximus - Elza Fonseca; María Vázquez; Laura Rodriguez-Lorenzo; Natalia Mallo; Ivone Pinheiro; Maria Lígia Sousa; Santiago Cabaleiro; Monica Quarato; Miguel Spuch-Calvar; Miguel A. Correa-Duarte; Juan José López-Mayán; Mick Mackey; et al. (Journal of Hazardous Materials, 2023)

Emergent role of critical interfaces in the dynamics of intensively managed landscapes - Praveen Kumar; Alison Anders; Erin Bauer; Neal E. Blair; Molly Cain; Ashlee Dere; Jennifer Druhan; Timothy Filley; Christos Giannopoulos; Allison E. Goodwell; David Grimley; Diana Karwan; et al. (Earth-Science Reviews, 2023)

Long-term e-cigarette aerosol exposure causes pulmonary emphysema in adult female and male mice - Andrea Jazel Rodriguez-Herrera; Ana Beatriz Farias de Souza; Thalles de Freitas Castro; Pedro Alves Machado-Junior; Elena Cecilia Marcano-Gomez; Tatiana Prata Menezes; Maria Laura da Cruz Castro; André Talvani; Daniela Caldeira Costa; Sílvia Dantas Cangussú; Frank Silva Bezerra (Regulatory Toxicology and Pharmacology, 2023)

HBM4EU-MOM: Prenatal methylmercury-exposure control in five countries through suitable dietary advice for pregnancy – Study design and characteristics of participants - Andromachi Katsonouri; Catherine Gabriel; Marta Esteban López; Sonia Namorado; Thorhallur I. Halldorsson; Janja Snoj Tratnik; Laura Rodriguez Martin; Achilleas Karakoltzidis; Anthoula Chatzimpaloglou; Despina Giannadaki; Elena Anastasi; Anthi Thoma; et al. (International Journal of Hygiene and Environmental Health, 2023)

The potential effects of in vitro digestion on the physicochemical and biological characteristics of polystyrene nanoplastics - Lourdes Vela; Aliro Villacorta; Tom Venus; Irina Estrela-Lopis; Susana Pastor; Alba García-Rodriguez; Laura Rubio; Ricard Marcos; Alba Hernández (Environmental Pollution, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Barriers and opportunities for waste pickers within solid waste management policy in Colombia - Alejandra Gómez-Maldonado; Laura Catalina Ospina-Espitia; Paul Rodríguez-Lesmes; Mayra Alejandra Rodríguez-Rodriguez (Waste Management, 2023)

Virulence, antimicrobial resistance, and dissemination of Campylobacter coli isolated from chicken carcasses in Brazil - Ana Beatriz Garcez Buiatte; Roberta Torres de Melo; Phelipe Augusto Borba Martins Peres; Clara Mariano Bastos; Ana Laura Grazziotin; Paulo Marcel Armendaris Rodriguez; Fabiano Barreto; Daise Aparecida Rossi (Food Control, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

Age-dependent effect of the IFIH1/MDA5 gene variants on the risk of critical COVID-19 - María G. Muñiz-Banciella; Guillermo M. Albaiceta; Laura Amado-Rodríguez; Estefanía Salgado del Riego; Inés López Alonso; Cecilia López-Martínez; Paula Martín-Vicente; Marta García-Clemente; Tamara Hermida-Valverde; Ana I. Enríquez-Rodriguez; Cristina Hernández-González; Elías Cuesta-Llavona; et al. (Immunogenetics, 2023)

Human urinary arsenic species, associated exposure determinants and potential health risks assessed in the HBM4EU Aligned Studies - Jurgen Buekers; Kirsten Baken; Eva Govarts; Laura Rodriguez Martin; Nina Vogel; Marike Kolossa-Gehring; Zdenka Šlejkovec; Ingrid Falnoga; Milena Horvat; Sanna Lignell; Anna Karin Lindroos; Loïc Rambaud; et al. (International Journal of Hygiene and Environmental Health, 2023)

Prenatal exposure to persistent organic pollutants and changes in infant growth and childhood growth trajectories - Anran Cai; Lützen Portengen; Eva Govarts; Laura Rodriguez Martin; Greet Schoeters; Juliette Legler; Roel Vermeulen; Virissa Lenters; Sylvie Remy (Chemosphere, 2023)

Multimodal study of the impact of stimulation pH on shale pore structure, with an emphasis on organics behavior in alkaline environments - Bryan X. Medina-Rodriguez; Laura Frouté; Vladimir Alvarado; Anthony R. Kovscek (Fuel, 2023)

Examining the Ability of CMIP6 Models to Reproduce the Upwelling SST Imprint in the Eastern Boundary Upwelling Systems - Rubén Varela; Maite DeCastro; Laura Rodriguez-Diaz; João Miguel Dias; Moncho Gómez-Gesteira (Journal of Marine Science and Engineering, 2022)
Knowing future changes in the sea surface temperature (SST) is of vital importance since they can affect marine ecosystems, especially in areas of high productivity such as the Eastern Boundary Upwelling Systems (EBUS). In this sense, it is key to have fine resolution models to study the SST patterns as close as possible to the coast where the upwelling influence is greater. Thus, the main objective of the present work is to assess the ability of 23 General Circulation Models (GCMs) from phase six of the Coupled Model Intercomparison Project (CMIP6) in reproducing the upwelling SST imprint in the EBUS through a comparison with the Optimum Interpolation of Sea Surface Temperature (OISST ¼) database of the National Oceanic and Atmospheric Administration for the common period of 1982–2014. The results have shown that most of the CMIP6 GCMs overestimate nearshore SST for all the EBUS with the exception of Canary. Overall, the models with better resolution showed lower Normalized Root Mean Squared Error (NRMSE) and Normalized Bias (NBias), although the ability of the models is dependent on the study area. Thus, the most suitable models for each EBUS are the CNRM-HR, GFDL-CM4, HadGEM-MM, CMCC-VHR4, and EC-Earth3P for Canary; CESM1-HR, CMCC-VHR4, ECMWF-HR, and HadGEM-HM for Humboldt; and HadGEM-HH and HadGEM-HM for California. In the case of Benguela, no model adequately reproduces the SST imprint under the conditions established in the present study.

Monocyte-to-Lymphocyte Ratio in Clot Analysis as a Marker of Cardioembolic Stroke Etiology - Jesús Juega; Carlos Palacio-Garcia; Maite Rodriguez; Matias Deck; David Rodriguez-Luna; Manuel Requena; Álvaro García-Tornel; Noelia Rodriguez-Villatoro; Marta Rubiera; Sandra Boned; Marian Muchada; Marc Ribo; et al. (Translational Stroke Research, 2022)

Oral Medicine Experience and Attitudes Toward Oral Cancer: An Evaluation of Dentists Working in Primary Health Care - Jéssica Rodriguez Strey; Michelle Roxo-Gonçalves; Bianca Dutra Guzenski; Marco Antonio Trevizani Martins; Juliana Romanini; Maria Antonia Zancanaro de Figueiredo; Otávio Pereira D’Ávila; Marcelo Rodrigues Gonçalves; Roberto Nunes Umpierre; Erno Harzheim; Laura de Campos Hildebrand; Vinicius Coelho Carrard (Journal of Cancer Education, 2022)

FishShapes v1: Functionally relevant measurements of teleost shape and size on three dimensions - Samantha A. Price; Sarah T. Friedman; Katherine A. Corn; Olivier Larouche; Kasey Brockelsby; Anna J. Lee; Maya Nagaraj; Nick G. Bertrand; Mailee Danao; Megan C. Coyne; John R. Estrada; Rachel Friedman; et al. (Ecology, 2022)
Teleost fishes account for 96% of all fish species and exhibit a spectacular variety of body forms. Teleost lineages range from deep bodied to elongate (e.g., eels, needlefish), laterally compressed (e.g., ribbonfish) to globular (e.g., pufferfish), and include uniquely shaped lineages such as seahorses, flatfishes, and ocean sunfishes. Adaptive body shape convergence within fishes has long been hypothesized but the nature of the relationships between fish form and ecological and environmental variables remain largely unknown at the macroevolutionary scale. To facilitate the investigation of the interacting factors influencing teleost body shape evolution we measured eight functionally relevant linear traits on adult‐sized specimens along with specimen mass. Linear measurements of standard length, maximum body depth, maximum fish width, lower jaw length, mouth width, head depth, minimum caudal peduncle depth, and minimum caudal peduncle width were taken in millimeters with calipers, or tape measures for oversized specimens. We measured these traits on a total of 16,523 specimens (1–3 specimens per species) at the Smithsonian National Museum of Natural History and took approximately 7000 person hours of data collection to complete. The data went through a three‐step error‐checking process to clean and validate the data and then species averages were calculated. We present the complete specimen data set, which encompasses approximately one‐fifth of extant teleost species diversity, spanning ~90% of teleost families and ~96% of orders. The species and family names are compatible with the taxonomy used by FishBase and the order information with the phylogenetically informed taxonomy of Betancur‐R and colleagues published in 2014. This dataset is licensed under Creative Commons CC0 1.0 Universal (CC0 1.0) but please cite this paper when using the data or a subset of it.

Correction to: Propolis extract combined with oregano essential oil applied to lima bean seeds against Sclerotinia sclerotiorum - Irene Laura Cibanal; Leticia Andrea Fernández; Silvana Andrea Rodriguez; Cecilia Noemí Pellegrini; Liliana María Gallez (European Journal of Plant Pathology, 2022)

Propolis extract combined with oregano essential oil applied to lima bean seeds against Sclerotinia sclerotiorum - Irene Laura Cibanal; Leticia Andrea Fernández; Silvana Andrea Rodriguez; Cecilia Noemí Pellegrini; Liliana María Gallez (European Journal of Plant Pathology, 2022)

The Colombian geochronological database (CGD) - Andres F. Rodriguez-Corcho; Yamirka Rojas-Agramonte; Johana A. Barrera-Gonzalez; Maria P. Marroquin-Gomez; Sarah Bonilla-Correa; David Izquierdo-Camacho; Sofia M. Delgado-Balaguera; David Cartwright-Buitrago; Maria D. Muñoz-Granados; William G. Carantón-Mateus; Alejandro Corrales-García; Andrés F. Laverde-Martinez; et al. (International Geology Review, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Muscular carnosine is a marker for cardiorespiratory fitness and cardiometabolic risk factors in men with type 1 diabetes - Laura Brugnara; Ana Isabel García; Serafín Murillo; Josep Ribalta; Guerau Fernandez; Susanna Marquez; Miguel Angel Rodriguez; Maria Vinaixa; Núria Amigó; Xavier Correig; Susana Kalko; Jaume Pomes; et al. (European Journal of Applied Physiology, 2022)

Fine Scale Microevolutionary and Demographic Processes Shaping a Wild Metapopulation Dynamics of the South American Fruit Fly Anastrepha fraterculus - Damián Freilij; Laura I. Ferreyra; Juan C. Vilardi; Angeles I. Rodriguez; Paula Gómez-Cendra (Neotropical Entomology, 2022)

Reduced mtDNA Copy Number in the Prefrontal Cortex of C9ORF72 Patients - Maria Isabel Alvarez-Mora; Petar Podlesniy; Teresa Riazuelo; Laura Molina-Porcel; Ellen Gelpi; Laia Rodriguez-Revenga (Molecular Neurobiology, 2022)

The human hepatocyte TXG-MAPr: gene co-expression network modules to support mechanism-based risk assessment - Giulia Callegaro; Steven J. Kunnen; Panuwat Trairatphisan; Solène Grosdidier; Marije Niemeijer; Wouter den Hollander; Emre Guney; Janet Piñero Gonzalez; Laura Furlong; Yue W. Webster; Julio Saez-Rodriguez; Jeffrey J. Sutherland; et al. (Archives of Toxicology, 2021)
Mechanism-based risk assessment is urged to advance and fully permeate into current safety assessment practices, possibly at early phases of drug safety testing. Toxicogenomics is a promising source of mechanisms-revealing data, but interpretative analysis tools specific for the testing systems (e.g. hepatocytes) are lacking. In this study, we present the TXG-MAPr webtool (available at https://txg-mapr.eu/WGCNA_PHH/TGGATEs_PHH/ ), an R-Shiny-based implementation of weighted gene co-expression network analysis (WGCNA) obtained from the Primary Human Hepatocytes (PHH) TG-GATEs dataset. The 398 gene co-expression networks (modules) were annotated with functional information (pathway enrichment, transcription factor) to reveal their mechanistic interpretation. Several well-known stress response pathways were captured in the modules, were perturbed by specific stressors and showed preservation in rat systems (rat primary hepatocytes and rat in vivo liver), with the exception of DNA damage and oxidative stress responses. A subset of 87 well-annotated and preserved modules was used to evaluate mechanisms of toxicity of endoplasmic reticulum (ER) stress and oxidative stress inducers, including cyclosporine A, tunicamycin and acetaminophen. In addition, module responses can be calculated from external datasets obtained with different hepatocyte cells and platforms, including targeted RNA-seq data, therefore, imputing biological responses from a limited gene set. As another application, donors’ sensitivity towards tunicamycin was investigated with the TXG-MAPr, identifying higher basal level of intrinsic immune response in donors with pre-existing liver pathology. In conclusion, we demonstrated that gene co-expression analysis coupled to an interactive visualization environment, the TXG-MAPr, is a promising approach to achieve mechanistic relevant, cross-species and cross-platform evaluation of toxicogenomic data.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Lithospheric density structure of the southern Central Andes constrained by 3D data-integrative gravity modelling - Constanza Rodriguez Piceda; Magdalena Scheck Wenderoth; Maria Laura Gomez Dacal; Judith Bott; Claudia Beatriz Prezzi; Manfred R. Strecker (International Journal of Earth Sciences, 2021)
The southern Central Andes (SCA) (between 27° S and 40° S) is bordered to the west by the convergent margin between the continental South American Plate and the oceanic Nazca Plate. The subduction angle along this margin is variable, as is the deformation of the upper plate. Between 33° S and 35° S, the subduction angle of the Nazca plate increases from sub-horizontal (< 5°) in the north to relatively steep (~ 30°) in the south. The SCA contain inherited lithological and structural heterogeneities within the crust that have been reactivated and overprinted since the onset of subduction and associated Cenozoic deformation within the Andean orogen. The distribution of the deformation within the SCA has often been attributed to the variations in the subduction angle and the reactivation of these inherited heterogeneities. However, the possible influence that the thickness and composition of the continental crust have had on both short-term and long-term deformation of the SCA is yet to be thoroughly investigated. For our investigations, we have derived density distributions and thicknesses for various layers that make up the lithosphere and evaluated their relationships with tectonic events that occurred over the history of the Andean orogeny and, in particular, investigated the short- and long-term nature of the present-day deformation processes. We established a 3D model of lithosphere beneath the orogen and its foreland (29° S–39° S) that is consistent with currently available geological and geophysical data, including the gravity data. The modelled crustal configuration and density distribution reveal spatial relationships with different tectonic domains: the crystalline crust in the orogen (the magmatic arc and the main orogenic wedge) is thicker (~ 55 km) and less dense (~ 2900 kg/m 3 ) than in the forearc (~ 35 km, ~ 2975 kg/m 3 ) and foreland (~ 30 km, ~ 3000 kg/m 3 ). Crustal thickening in the orogen probably occurred as a result of stacking of low-density domains, while density and thickness variations beneath the forearc and foreland most likely reflect differences in the tectonic evolution of each area following crustal accretion. No clear spatial relationship exists between the density distribution within the lithosphere and previously proposed boundaries of crustal terranes accreted during the early Paleozoic. Areas with ongoing deformation show a spatial correlation with those areas that have the highest topographic gradients and where there are abrupt changes in the average crustal-density contrast. This suggests that the short-term deformation within the interior of the Andean orogen and its foreland is fundamentally influenced by the crustal composition and the relative thickness of different crustal layers. A thicker, denser, and potentially stronger lithosphere beneath the northern part of the SCA foreland is interpreted to have favoured a strong coupling between the Nazca and South American plates, facilitating the development of a sub-horizontal slab.

α-Tocopherol Acetate Attenuates Mitochondrial Oxygen Consumption and Maintains Primitive Cells within Mesenchymal Stromal Cell Population - Darija Loncaric; Laura Rodriguez; Christelle Debeissat; Nicolas Touya; Veronique Labat; Arnaud Villacreces; Anne-Karine Bouzier-Sore; Jean-Max Pasquet; Philippe Brunet de la Grange; Marija Vlaski-Lafarge; Sonja Pavlovic; Zoran Ivanovic (Stem Cell Reviews and Reports, 2021)

An intrapopulational study of organic compounds and biomechanical properties of the shell of the Antarctic bivalve Laternula elliptica (P. P. King, 1832) at King George Island - M. Roberto García-Huidobro; María Josefina Poupin; Cristóbal Urrutia; Alejandro B. Rodriguez-Navarro; Christian Grenier; Juan F. Vivanco; Laura Ramajo; Isabel Benjumeda; Nelson A. Lagos; Marco A. Lardies (Polar Biology, 2021)

Optimization of a Multiple Injection System in a Marine Diesel Engine through a Multiple-Criteria Decision-Making Approach - Maria Isabel Lamas; Laura Castro-Santos; Carlos G. Rodriguez (Journal of Marine Science and Engineering, 2020)
In this work, a numerical model was developed to analyze the performance and emissions of a marine diesel engine, the Wärtsilä 6L 46. This model was validated using experimental measurements and was employed to analyze several pre-injection parameters such as pre-injection rate, duration, and starting instant. The modification of these parameters may lead to opposite effects on consumption and/or emissions of nitrogen oxides (NOx), carbon monoxide (CO), and hydrocarbons (HC). According to this, the main goal of the present work is to employ a multiple-criteria decision-making (MCDM) approach to characterize the most appropriate injection pattern. Since determining the criteria weights significantly influences the overall result of a MCDM problem, a subjective weighting method was compared with four objective weighting methods: entropy, CRITIC (CRiteria Importance Through Intercriteria Correlation), variance, and standard deviation. The results showed the importance of subjectivism over objectivism in MCDM analyses. The CRITIC, variance, and standard deviation methods assigned more importance to NOx emissions and provided similar results. Nevertheless, the entropy method assigned more importance to consumption and provided a different injection pattern.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Heat stress effects on bovine sperm cells: a chronological approach to early findings - Laura Nataly Garcia-Oliveros; Rubens Paes de Arruda; Leonardo Batissaco; Vitor Hugo Guilger Gonzaga; Vinícius José Moreira Nogueira; Shirley Andrea Florez-Rodriguez; Flávia dos Santos Almeida; Maíra Bianchi Rodrigues Alves; Sâmara Cristine Costa Pinto; Marcilio Nichi; João Diego de Agostini Losano; Giulia Kiyomi Vechiato Kawai; et al. (International Journal of Biometeorology, 2020)

Dermal exposure to the UV filter benzophenone-3 during early pregnancy affects fetal growth and sex ratio of the progeny in mice - Clarisa Guillermina Santamaria; Nicole Meyer; Anne Schumacher; María Laura Zenclussen; Carla Mariela Teglia; María Julia Culzoni; Ana Claudia Zenclussen; Horacio Adolfo Rodriguez (Archives of Toxicology, 2020)

Environmental factors driving the distribution of the tropical coral Pavona varians : Predictions under a climate change scenario - Laura Rodriguez; Juan José García; Fernando Tuya; Brezo Martínez (Marine Ecology, 2020)
Climate change causes shifts in the geographical distribution boundaries of many organisms. Modelling techniques predict the distribution of species by relating climatic and physical factors with species' presence records, including potential extinction areas and new potential areas of colonization, under predicted climatic scenarios. In this study, we initially explored which environmental variables most influenced the distribution of Pavona varians , a hermatypic coral from the equatorial Indian and the Pacific Ocean, which is categorized as ‘Least Concern’ by the UICN. The most influential variables were the minimum and maximum sea surface temperature, the diffuse water attenuation and the cloud cover. These variables were used to predict habitat suitability of P. varians under a current and a future (A1B IPPC) scenario using MaxEnt. Despite P. varians is an opportunistic species, with a well‐known resistance to environmental stress, the model predicted a massive decline in the suitability of its habitat in all areas by the year 2100. The information obtained by this study can be used to support the conservation decision making process to improve the preservation of the species.

Numerical Analysis of NOx Reduction Using Ammonia Injection and Comparison with Water Injection - María Isabel Lamas Galdo; Laura Castro-Santos; Carlos G. Rodriguez Vidal (Journal of Marine Science and Engineering, 2020)
This work analyzes NOx reduction in a marine diesel engine using ammonia injection directly into the cylinder and compares this procedure with water injection. A numerical model based on the so-called inert species method was applied. It was verified that ammonia injection can provide almost 80% NOx reduction for the conditions analyzed. Furthermore, it was found that the effectiveness of the chemical effect using ammonia is extremely dependent on the injection timing. The optimum NOx reduction was obtained when ammonia is injected during the expansion stroke, while the optimum injection timing using water is near top dead center. Chemical, thermal, and dilution effects of both ammonia and water injection were compared. The chemical effect was dominant in the case of ammonia injection. On the other hand, water injection reduces NOx through dilution and, more significantly, through a thermal effect.

Opioid-Induced Hyperalgesia Is Associated with Dysregulation of Circadian Rhythm and Adaptive Immune Pathways in the Mouse Trigeminal Ganglia and Nucleus Accumbens - Pan Zhang; Laura S. Moye; Bruce R. Southey; Isaac Dripps; Jonathan V. Sweedler; Amynah Pradhan; Sandra L. Rodriguez-Zas (Molecular Neurobiology, 2019)

Improving Research Literacy in Diverse Minority Populations with a Novel Communication Tool - Melissa A. Simon; Rodney Haring; Elisa M. Rodriguez; Evelyn González; Judith S. Kaur; Marcie Kirschner; Laura Tom; Catherine A. O’Brian; Mira L. Katz (Journal of Cancer Education, 2019)

Atlantic corals under climate change: modelling distribution shifts to predict richness, phylogenetic structure and trait-diversity changes - Laura Rodriguez; Brezo Martínez; Fernando Tuya (Biodiversity and Conservation, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

The Neuronal Ischemic Tolerance Is Conditioned by the Tp53 Arg72Pro Polymorphism - Maria E. Ramos-Araque; Cristina Rodriguez; Rebeca Vecino; Elisa Cortijo Garcia; Mercedes de Lera Alfonso; Mercedes Sanchez Barba; Laura Colàs-Campàs; Francisco Purroy; Juan F. Arenillas; Angeles Almeida; Maria Delgado-Esteban (Translational Stroke Research, 2019)
Cerebral preconditioning (PC) confers endogenous brain protection after stroke. Ischemic stroke patients with a prior transient ischemic attack (TIA) may potentially be in a preconditioned state. Although PC has been associated with the activation of pro-survival signals, the mechanism by which preconditioning confers neuroprotection is not yet fully clarified. Recently, we have described that PC-mediated neuroprotection against ischemic insult is promoted by p53 destabilization, which is mediated by its main regulator MDM2. Moreover, we have previously described that the human Tp53 Arg72Pro single nucleotide polymorphism (SNP) controls susceptibility to ischemia-induced neuronal apoptosis and governs the functional outcome of patients after stroke. Here, we studied the contribution of the human Tp53 Arg72Pro SNP on PC-induced neuroprotection after ischemia. Our results showed that cortical neurons expressing the Pro72-p53 variant exhibited higher PC-mediated neuroprotection as compared with Arg72-p53 neurons. PC prevented ischemia-induced nuclear and cytosolic p53 stabilization in Pro72-p53 neurons. However, PC failed to prevent mitochondrial p53 stabilization, which occurs in Arg72-p53 neurons after ischemia. Furthermore, PC promoted neuroprotection against ischemia by controlling the p53/active caspase-3 pathway in Pro72-p53, but not in Arg72-p53 neurons. Finally, we found that good prognosis associated to TIA within 1 month prior to ischemic stroke was restricted to patients harboring the Pro72 allele. Our findings demonstrate that the Tp53 Arg72Pro SNP controls PC-promoted neuroprotection against a subsequent ischemic insult by modulating mitochondrial p53 stabilization and then modulates TIA-induced ischemic tolerance.

The voltage-sensitive cardiac M2 muscarinic receptor modulates the inward rectification of the G protein-coupled, ACh-gated K+ current - Pedro D. Salazar-Fajardo; Iván A. Aréchiga-Figueroa; Ana Laura López-Serrano; Julio C. Rodriguez-Elias; Javier Alamilla; José A. Sánchez-Chapula; Martin Tristani-Firouzi; Ricardo A. Navarro-Polanco; Eloy G. Moreno-Galindo (Pflügers Archiv - European Journal of Physiology, 2018)

Vinasse irrigation: effects on soil fertility and arbuscular mycorrhizal fungi population - Ana Lorena Sanchez-Lizarraga; Valeria Arenas-Montaño; Erika Nahomy Marino-Marmolejo; Luc Dendooven; Jesus Bernardino Velazquez-Fernandez; Gustavo Davila-Vazquez; Jacobo Rodriguez-Campos; Laura Hernández-Cuevas; Silvia Maribel Contreras-Ramos (Journal of Soils and Sediments, 2018)

The transboundariness approach and prioritization of transboundary aquifers between Mexico and Texas - Rosario Sanchez; Laura Rodriguez; Cecilia Tortajada (Ambio, 2018)

Storm impacts on alpine lakes: Antecedent weather conditions matter more than the event intensity - Marie‐Elodie Perga; Rosalie Bruel; Laura Rodriguez; Yann Guénand; Damien Bouffard (Global Change Biology, 2018)
Extreme weather events may be just as important as gradual trends for the long‐term trajectories of ecosystems. For alpine lakes, which are exposed to both exacerbated atmospheric warming and intense episodic weather events, future conditions might not be appropriately forecast by only climate change trends, i.e. warming, if extreme events have the potential to deflect their thermal and metabolic states from their seasonal ranges. We used high‐frequency monitoring data over three open‐water seasons with a one‐dimensional hydrodynamic model of the high‐altitude Lake Muzelle (France) to show that rainstorms or windstorms, notwithstanding their intensity, did not trigger long‐lasting consequences to the lake characteristics when light penetration into the lake was not modified. In contrast, storms associated with high turbidity input from the watershed (“turbid storms”) strongly modified the lacustrine hydrodynamics and metabolism for the rest of the open‐water season through reduced light penetration. The long‐lasting effects of turbid storms were related to the inputs and in‐lake persistence of very light glacial suspensoids from the watershed. The occurrence of the observed turbid storms was not related to the wind or rain intensities during the events. Instead, the turbid storms occurred after dry and atypically warm spells, i.e. meteorological conditions expected to be more frequent in this alpine region in the upcoming decades. Consequently, storm events, notwithstanding their intensity, are expected to strongly imprint the future ecological status of alpine lakes under climate warming.

Endophytic biocatalysts with enoate reductase activity isolated from Mentha pulegium - Facundo Marconi; María Laura Umpiérrez; David Gonzalez; Sonia Rodríguez Giordano; Paula Rodriguez (World Journal of Microbiology and Biotechnology, 2018)

Erratum to: Effects of Hypoxia on Fish Survival and Oyster Growth in a Highly Eutrophic Estuary - Rikke Jeppesen; Miguel Rodriguez; Jenna Rinde; John Haskins; Brent Hughes; Laura Mehner; Kerstin Wasson (Estuaries and Coasts, 2018)

Effects of Hypoxia on Fish Survival and Oyster Growth in a Highly Eutrophic Estuary - Rikke Jeppesen; Miguel Rodriguez; Jenna Rinde; John Haskins; Brent Hughes; Laura Mehner; Kerstin Wasson (Estuaries and Coasts, 2018)

Music-related reward responses predict episodic memory performance - Laura Ferreri; Antoni Rodriguez-Fornells (Experimental Brain Research, 2017)

Integrating Science-Based Co-management, Partnerships, Participatory Processes and Stewardship Incentives to Improve the Performance of Small-Scale Fisheries - Kendra A. Karr; Rod Fujita; Ramon Carcamo; Lawrence Epstein; James R. Foley; José A. Fraire-Cervantes; Mauro Gongora; Ollin T. Gonzalez-Cuellar; Pablo Granados-Dieseldorff; Julius Guirjen; Amy H. Weaver; Héctor Licón-González; et al. (Frontiers in Marine Science, 2017)

Novel micromorphological features of wood and bark of Argentinean Simaroubaceae - Maria Noel Campagna; Martha Gattuso; Maria Laura Martinez; Maria Victoria Rodriguez; Osvaldo Di Sapio (New Zealand Journal of Botany, 2017)
Simaroubaceae is a family of about 22 genera and 100 species of mainly tropical and subtropical trees and shrubs and it is generally considered to be a heterogeneous group. In Argentina, Simaroubaceae is represented by three genera and four species, one of these is exotic: Ailanthus altissima (Mill.) Swingle while the other three are native: Castela coccinea Griseb., C. tweedii Planch. and Picrasma crenata (Vell.) Engl. Wood and bark anatomies of the Argentinean species were studied in an effort to find distinctive features for the genera and species within this family. Transverse, tangential and radial sections of the specimens were prepared and macerated according to conventional techniques; microscopic examination was performed by light microscopy and scanning electron microscopy. It was possible to make a key for the species and genera using a combination of qualitative (presence/absence of wood growth rings, porosity, abundance of parenchyma, occurrence of crystals, etc.), and quantitative features (vessels per square millimetre, tangential diameter of vessel lumina, etc.). The wood and bark characteristics obtained provide new evidence of the heterogeneous nature of the family. From an ecological point of view, according to vessel size, vessel number, mesomorphy and vulnerability index, the wood of the studied species belonging to Castela genus were characterised as xeromorphic, while the other genera were characterised as mesomorphic.

Matrix metalloproteinase-14 triggers an anti-inflammatory proteolytic cascade in endotoxemia - Alina Aguirre; Jorge Blázquez-Prieto; Laura Amado-Rodriguez; Inés López-Alonso; Estefanía Batalla-Solís; Adrián González-López; Moisés Sánchez-Pérez; Carlos Mayoral-Garcia; Ana Gutiérrez-Fernández; Guillermo M Albaiceta (Journal of Molecular Medicine, 2017)

Biodegradation of Diesel, Crude Oil and Spent Lubricating Oil by Soil Isolates of Bacillus spp. - Maddela Naga Raju; Rodriguez Leo; Sanaguano Salguero Herminia; Ricardo Ernesto Burgos Morán; Kadiyala Venkateswarlu; Scalvenzi Laura (Bulletin of Environmental Contamination and Toxicology, 2017)

A Catalogue of Marine Biodiversity Indicators - Heliana Teixeira; Torsten Berg; Laura Uusitalo; Karin Fürhaupter; Anna-Stiina Heiskanen; Krysia Mazik; Christopher P. Lynam; Suzanna Neville; J. German Rodriguez; Nadia Papadopoulou; Snejana Moncheva; Tanya Churilova; et al. (Frontiers in Marine Science, 2016)

Experimental and DFT characterization, antioxidant and anticancer activities of a Cu(II)–irbesartan complex: structure–antihypertensive activity relationships in Cu(II)–sartan complexes - María S. Islas; Alicia Luengo; Carlos A. Franca; Mercedes Griera Merino; Laura Calleros; Manuel Rodriguez-Puyol; Luis Lezama; Evelina G. Ferrer; Patricia A. M. Williams (JBIC Journal of Biological Inorganic Chemistry, 2016)

Grafting collagen on poly (lactic acid) by a simple route to produce electrospun scaffolds, and their cell adhesion evaluation - Alida Ospina-Orejarena; Ricardo Vera-Graziano; Maria Monica Castillo-Ortega; Juan Paulo Hinestroza; Mabel Rodriguez-Gonzalez; Laura Palomares-Aguilera; Marissa Morales-Moctezuma; Alfredo Maciel-Cerda (Tissue Engineering and Regenerative Medicine, 2016)

Biomineralization changes with food supply confer juvenile scallops ( Argopecten purpuratus ) resistance to ocean acidification - Laura Ramajo; Núria Marbà; Luis Prado; Sophie Peron; Marco A. Lardies; Alejandro B. Rodriguez‐Navarro; Cristian A. Vargas; Nelson A. Lagos; Carlos M. Duarte (Global Change Biology, 2016)
Future ocean acidification ( OA ) will affect physiological traits of marine species, with calcifying species being particularly vulnerable. As OA entails high energy demands, particularly during the rapid juvenile growth phase, food supply may play a key role in the response of marine organisms to OA . We experimentally evaluated the role of food supply in modulating physiological responses and biomineralization processes in juveniles of the Chilean scallop, Argopecten purpuratus, that were exposed to control ( pH ~ 8.0) and low pH ( pH ~ 7.6) conditions using three food supply treatments (high, intermediate, and low). We found that pH and food levels had additive effects on the physiological response of the juvenile scallops. Metabolic rates, shell growth, net calcification, and ingestion rates increased significantly at low pH conditions, independent of food. These physiological responses increased significantly in organisms exposed to intermediate and high levels of food supply. Hence, food supply seems to play a major role modulating organismal response by providing the energetic means to bolster the physiological response of OA stress. On the contrary, the relative expression of chitin synthase, a functional molecule for biomineralization, increased significantly in scallops exposed to low food supply and low pH , which resulted in a thicker periostracum enriched with chitin polysaccharides. Under reduced food and low pH conditions, the adaptive organismal response was to trade‐off growth for the expression of biomineralization molecules and altering of the organic composition of shell periostracum, suggesting that the future performance of these calcifiers will depend on the trajectories of both OA and food supply. Thus, incorporating a suite of traits and multiple stressors in future studies of the adaptive organismal response may provide key insights on OA impacts on marine calcifiers.

Assessment of the gross primary production dynamics of a Mediterranean holm oak forest by remote sensing time series analysis - Víctor Cicuéndez; Javier Litago; Margarita Huesca; Manuel Rodriguez-Rastrero; Laura Recuero; Silvia Merino-de-Miguel; Alicia Palacios-Orueta (Agroforestry Systems, 2015)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Environmental Effectors on the Inactivation of Human Adenoviruses in Water - Anna Carratalà; Marta Rusiñol; Jesús Rodriguez-Manzano; Laura Guerrero-Latorre; Regina Sommer; Rosina Girones (Food and Environmental Virology, 2013)

Transcriptome analysis of cytoplasmic male sterility and restoration in CMS-D8 cotton - Hideaki Suzuki; Laura Rodriguez-Uribe; Jiannong Xu; Jinfa Zhang (Plant Cell Reports, 2013)

First Report of Microcystins and Anatoxin-a Co-occurrence in San Roque Reservoir (Córdoba, Argentina) - Marcia Ruiz; Lucas Galanti; Ana Laura Ruibal; María Ines Rodriguez; Daniel Alberto Wunderlin; María Valeria Amé (Water, Air, & Soil Pollution, 2013)

The droughts of 1997 and 2005 in Amazonia: floodplain hydrology and its potential ecological and human impacts - Javier Tomasella; Patrícia F. Pinho; Laura S. Borma; José A. Marengo; Carlos A. Nobre; Olga R. F. O. Bittencourt; Maria C. R. Prado; Daniel A. Rodriguez; Luz A. Cuartas (Climatic Change, 2013)

Balance between apoptosis or survival induced by changes in extracellular-matrix composition in human mesangial cells: a key role for ILK-NFκB pathway - María del Nogal; Alicia Luengo; Gemma Olmos; Marina Lasa; Diego Rodriguez–Puyol; Manuel Rodriguez–Puyol; Laura Calleros (Apoptosis, 2012)

Antiviral compounds obtained from microalgae commonly used as carotenoid sources - Susana Santoyo; Laura Jaime; Merichel Plaza; Miguel Herrero; Irene Rodriguez-Meizoso; Elena Ibañez; Guillermo Reglero (Journal of Applied Phycology, 2012)

Modified Natural Clinoptilolite Detoxifies Small Mammal’s Organism Loaded with Lead II: Genetic, Cell, and Physiological Effects - Margarita Topashka-Ancheva; Michaela Beltcheva; Roumiana Metcheva; J. Antonio Heredia Rojas; Abraham O. Rodriguez-De la Fuente; Tsvetelina Gerasimova; Laura E. Rodríguez-Flores; Svetla E. Teodorova (Biological Trace Element Research, 2012)

Detection of somaclonal variants in somatic embryogenesis-regenerated plants of Vitis vinifera by flow cytometry and microsatellite markers - María Jesús Prado; Eleazar Rodriguez; Laura Rey; María Victoria González; Conceição Santos; Manuel Rey (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Late Holocene climate and environment of the SE Pampa grasslands, Argentina, inferred from biological indicators in shallow, freshwater Lake Nahuel Rucá - Silvina Stutz; C. Marcela Borel; Sonia L. Fontana; Laura del Puerto; Hugo Inda; Felipe García-Rodriguez; Marcela S. Tonello (Journal of Paleolimnology, 2010)

ATP-mediated cell–cell signaling in the organ of Corti: the role of connexin channels - Paromita Majumder; Giulia Crispino; Laura Rodriguez; Catalin Dacian Ciubotaru; Fabio Anselmi; Valeria Piazza; Mario Bortolozzi; Fabio Mammano (Purinergic Signalling, 2010)

Wolf–Hirschhorn syndrome-associated chromosome changes are not mediated by olfactory receptor gene clusters nor by inversion polymorphism on 4p16 - Marcella Zollino; Rosetta Lecce; Marina Murdolo; Daniela Orteschi; Giuseppe Marangi; Angelo Selicorni; Alina Midro; Giovanni Sorge; Giuseppe Zampino; Luigi Memo; Domenica Battaglia; Michael Petersen; et al. (Human Genetics, 2008)

Wolf–Hirschhorn syndrome-associated chromosome changes are not mediated by olfactory receptor gene clusters nor by inversion polymorphism on 4p16 - Marcella Zollino; Rosetta Lecce; Marina Murdolo; Daniela Orteschi; Giuseppe Marangi; Angelo Selicorni; Alina Midro; Giovanni Sorge; Giuseppe Zampino; Luigi Memo; Domenica Battaglia; Michael Petersen; et al. (Human Genetics, 2007)

Can Invasive Species Facilitate Native Species? Evidence of How, When, and Why These Impacts Occur - Laura F. Rodriguez (Biological Invasions, 2006)

The impacts of climate change in coastal marine systems - Christopher D. G. Harley; A. Randall Hughes; Kristin M. Hultgren; Benjamin G. Miner; Cascade J. B. Sorte; Carol S. Thornber; Laura F. Rodriguez; Lars Tomanek; Susan L. Williams (Ecology Letters, 2006)
Anthropogenically induced global climate change has profound implications for marine ecosystems and the economic and social systems that depend upon them. The relationship between temperature and individual performance is reasonably well understood, and much climate‐related research has focused on potential shifts in distribution and abundance driven directly by temperature. However, recent work has revealed that both abiotic changes and biological responses in the ocean will be substantially more complex. For example, changes in ocean chemistry may be more important than changes in temperature for the performance and survival of many organisms. Ocean circulation, which drives larval transport, will also change, with important consequences for population dynamics. Furthermore, climatic impacts on one or a few ‘leverage species’ may result in sweeping community‐level changes. Finally, synergistic effects between climate and other anthropogenic variables, particularly fishing pressure, will likely exacerbate climate‐induced changes. Efforts to manage and conserve living marine systems in the face of climate change will require improvements to the existing predictive framework. Key directions for future research include identifying key demographic transitions that influence population dynamics, predicting changes in the community‐level impacts of ecologically dominant species, incorporating populations’ ability to evolve (adapt), and understanding the scales over which climate will change and living systems will respond.

Sour-Taste Tolerance in Four Species of Nonhuman Primates - Matthias Laska; Heinz-Peter Scheuber; Laura Teresa Hernandez Salazar; Ernesto Rodriguez Luna (Journal of Chemical Ecology, 2003)

Gustatory Responsiveness to Polycose in Four Species of Nonhuman Primates - Matthias Laska; Stefanie Kohlmann; Hans-Peter Scheuber; Laura Teresa Hernandez Salazar; Ernesto Rodriguez Luna (Journal of Chemical Ecology, 2001)

Food Preferences and Nutrient Composition in Captive Spider Monkeys, Ateles geoffroyi - Matthias Laska; Laura Teresa Hernandez Salazar; Ernesto Rodriguez Luna (International Journal of Primatology, 2000)

Gustatory Responsiveness to food-associated acids in the spider monkey (Ateles geoffroyi) - Matthias Laska; Laura Teresa Hernandez Salazar; Ernesto Rodriguez Luna; Robyn Hudson (Primates, 2000)